Detection of Cortical and Deep Gray Matter Lesions in Multiple Sclerosis Using DIR and FLAIR at 3T. Issue 2 (22nd December 2020) - Park, Charlie C.; Thongkham, Dean W.; Sadigh, Gelareh; Saindane, Amit M.; Chu, Renxin; Bakshi, Rohit; Allen, Jason W.; Hu, Ranliang
ABSTRACT: BACKGROUND AND PURPOSE: The comparative detection rates of deep gray matter (GM) multiple sclerosis (MS) lesions using double inversion recovery (DIR) and fluid‐attenuated inversion‐recovery (FLAIR) on 3T MR imaging remain unknown. We aimed to assess the detectability of cortical and deep GM MS lesions using DIR and FLAIR on 3T clinical exams and evaluate the relationship between deep GM lesions and brain atrophy. METHODS: One hundred fifty consecutive MS patients underwent routine brain MRI that included 3D DIR and 2D T2 FLAIR on the same 3T scanner. Three neuroradiologists independently reviewed all exams for cortical and deep GM lesions. Statistical parametric mapping (SPM) and FMRIB software library (FSL)‐FIRST pipelines were used to determine normalized whole brain and deep GM volumes. RESULTS: A total of 65 cortical and 98 deep lesions were detected on DIR versus 24 and 20, respectively, on FLAIR. Among all 150 patients, the number and percentage of patients with GM lesions on DIR and FLAIR were as follows: cortical 43 (28.7%) versus 24 (16.0%) ( P < .001), thalamus 47 (31.3%) versus 20 (13.3%) ( P  < .001), putamen 10 (6.7%) versus 3 (2.0%) ( P = .02), globus pallidus 9 (6.0%) versus 3 (1.3%) ( P = .02), and caudate 5 (3.3%) versus 1 (0.7%) ( P = .125). Presence of deep GM lesions weakly correlated with deep GM volume fractions. CONCLUSION: Deep GM MS lesions can be detected using routine clinical brain MRI including DIR and FLAIR at 3T. Future studies to optimize these sequences may improve the detection rates of cortical and deep GM lesions. The presence of GM lesions showed weak correlation with GM atrophy.